2004
DOI: 10.18195/issn.0313-122x.67.2004.007-037
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic invertebrate assemblages of wetlands and rivers in the wheatbelt region of Western Australia

Abstract: -A biological survey of wetlands in the Wheatbelt and adjacent coastal areas of south-west Western Australia was undertaken to document the extent and distribution of the region's aquatic invertebrate diversity. Two hundred and thirty samples were collected from 223 wetlands, including freshwater swamps and lakes, salinised wetlands, springs, rivers, artificial wetlands (farm dams and small reservoirs), saline playas and coastal salt lakes between 1997 and 2000. The number of aquatic invertebrates identified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 79 publications
7
79
0
Order By: Relevance
“…However, many Coleoptera in inland southwest WA appear to be relatively salt tolerant, and the same correlation was not found in this study (over 0-8 or 0-20 gl -1 TDS) or in other studies in the same region (Kay et al, 2001;Bailey et al, 2002;Pinder et al, 2004Pinder et al, , 2005. It is also possible that salinity differences in abundances of Coleoptera, between mesocosm and field samples, may partially be due to some field Coleoptera having developed from eggs within water bodies, whereas all Coleoptera colonised mesocosms as adults.…”
Section: Salinity Colonisation Behaviour and Insects In The Fieldsupporting
confidence: 79%
See 1 more Smart Citation
“…However, many Coleoptera in inland southwest WA appear to be relatively salt tolerant, and the same correlation was not found in this study (over 0-8 or 0-20 gl -1 TDS) or in other studies in the same region (Kay et al, 2001;Bailey et al, 2002;Pinder et al, 2004Pinder et al, , 2005. It is also possible that salinity differences in abundances of Coleoptera, between mesocosm and field samples, may partially be due to some field Coleoptera having developed from eggs within water bodies, whereas all Coleoptera colonised mesocosms as adults.…”
Section: Salinity Colonisation Behaviour and Insects In The Fieldsupporting
confidence: 79%
“…Ephemeral water bodies are characteristic of the Wheatbelt, where they show a range of salinities, especially in areas affected by secondary salinisation, making them ideal to investigate how salinity affects the colonisation and oviposition behaviour of insects. Numerous studies have investigated how salinity influences the distribution of aquatic organisms by examining patterns in species occurrence (Halse, 1981;Bunn & Davies, 1992;Kay et al, 2001;Williams, 2003;Halse et al, 2004;Marshall & Bailey, 2004;Pinder et al, 2004;Piscart et al, 2005a) and salt sensitivity (Roberts, 1996;Blasius & Merritt, 2002;Kefford et al 2003;Jeffery et al 2005;Hassell et al, 2006;Zalizniak et al, 2006). Studies have found a range of invertebrate fauna, such as the disease vector Ae.…”
Section: Introductionmentioning
confidence: 99%
“…These water quality conditions were tolerated by only very hardy species, as increased salinity and acidity of sites impacted by deep drainage led to a sharp decline in species richness, and significant changes in macro-invertebrate community composition downstream of the drain. Kay et al (2001) showed a general tendency for family richness in Wheatbelt streams to decrease with increasing salinity, whilst Pinder et al (2004Pinder et al ( , 2005 further demonstrated that salinity has a major influence on the distribution of aquatic invertebrates in the Wheatbelt. They showed that the salinity range of 10-20 ppt (g l −1…”
Section: Impacts Of High Salinity and Acidity On Biodiversitymentioning
confidence: 95%
“…The conversion between conductivity and salinity was performed using a conversion factor of 0.64. Following Pinder et al (2004), water was considered 'fresh' when salinity was <3 ppt, 'subsaline' when 3-10 ppt, and saline when >10 ppt. Values greater than 100 ppt signify hypersaline conditions.…”
Section: Measurement Of Water Quality Variablesmentioning
confidence: 99%
“…In Australia, secondary salinisation is principally caused by rising watertables as a consequence of reduced evapotranspiration following changes in land use, typically land clearing for agriculture. The south-west corner of Australia, where~80-90% of the land has been cleared, is a hot spot in terms of secondary salinisation (NLWRA 2001;Halse et al 2003;Pinder et al 2004). As a result, most of the freshwater ecosystems in south-western Australia are affected by increasing salinity, with 56% having become brackish (1.0-2.0 g L -1 ) or saline (>2.0 g L -1 ) (see Mayer et al 2005).…”
Section: Salinity As a Threatening Processmentioning
confidence: 99%